Synthesis of catalyst comprising high purity NU-86 zeolite and iron for conversion of NOx and N2O
By preparing catalysts based on NU-86 breaked and iron, the problem of difficulty in restoration of NOX and N2O is solved by the existing technology, and the excellent transformation performance of the specific temperature range and the superiority of the N2O directly decompose N2O.
Patent Information
- Application Number
- CN202380047201.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-17
- Filing Date
- 2023-06-09
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art is difficult to effectively reduce nitrogen oxides (NOx) and nitrous oxides (N2O) produced in combustion and industrial flue gases simultaneously, especially under strict environmental standards.
By preparing a catalyst based on the NU-86 blood and iron, using specific synthetic methods and ion exchange steps to improve the performance of catalysts, so that they can show excellent NOX and N2O conversion capabilities within the temperature range of 300 to 500 ° C.
This catalyst shows excellent performance in terms of NOX and N2O at the same time, especially within the temperature range of 300 to 500 ° C. Its performance is better than the use of existing technology catalysts, and the nature of N2O can be directly decomposed and can also be very superior.
Smart Images

Figure CN119384395A_ABST
Abstract
Description
Technical Field
[0001] The present invention provides a process for preparing a catalyst based on Nu-86 zeolite and at least one transition metal, especially iron, a catalyst prepared or preparable by the process, and its use for the simultaneous reduction of nitrogen oxides (NOx) and nitrous oxide (N2O), in particular in combustion processes and industrial processes, such as the production of nitric acid and adipic acid. Background Art
[0002] Nitrogen oxide (NOx) emissions from combustion are of great concern to society as they are responsible for health problems, ground-level ozone, acid rain and smog. In order to limit the impact on the environment and health, government authorities set increasingly stringent standards. To achieve these goals, highly efficient pollution control systems such as three-way catalysts or selective catalytic reduction catalysts (acronym "SCR") have been developed for equipping transport units. However, the selectivity of these systems leads to nitrous oxide (N2O) emissions, which are not uncommon. Nitrous oxide is the third largest contributor to radiative forcing after carbon dioxide (CO2) and methane (CH4). In addition to affecting stratospheric ozone, according to the fourth IPCC report, a certain amount of N2O in the atmosphere has an impact on global warming 298 times that of the same amount of CO2 over 100 years.
[0003] Ammonia is considered an important decarbonization fuel. However, the combustion of ammonia (or H2 / NH3 mixture) may emit large amounts of N2O, NOx and NH3 in the exhaust gas.
[0004] Other industries also have high NOx and N2O emissions; the nitric acid industry is one of the main sources of nitrogen dioxide (N2O). N2O is formed as a byproduct of the oxidation of ammonia over a Pt / Rh catalyst. NOx is the main product at the outlet of the Pt / Rh catalyst and is subsequently absorbed by water to form nitric acid. The efficiency of the absorption step is not 100%, so NOx emissions are generated at the outlet (100 to 500 ppm).
[0005] Therefore, it is necessary to treat NOx and N2O in applications related to decarbonization and industrial flue gas.
[0006] The treatment of NOx has been the subject of a great deal of research in industry and transportation. For the treatment of N2O, several catalysts have been investigated depending on their effective temperature. Noble metals have very good efficiency around 250 °C, but are expensive and tend to be deactivated in the presence of inhibitors (CO, H2O, NOx, O2, etc.), which is inconsistent with the constraints of nitric acid or adipic acid production. Zeolites are relatively low cost and have a very large extended surface area, so good catalytic systems can be obtained by adding transition metals, especially iron. The research of Sádovská et al. (Sádovská, G., Bernauer, M., Bernauer, B., Tabor, E., Vondrová, A., & Sobalík, Z, (2018), On the mechanism of high-temperature N2O decomposition over Fe-FER in the presence of NO, Catalysis Communications, 112, 58-62) showed that iron-containing FER zeolites have very impressive performance qualities in N2O decomposition and have a positive effect on the decomposition process of NO in the temperature range of 600-900°C. The FER structure containing an Al pair resists high temperature 900°C deN2O conditions (Tabor, E., Mlekodaj, K., Sádovská, G., Bernauer, M., Klein, P., Sazama, P., ... & Sobalík, Z. (2019), Structural stability of metal containing ferrierite under the conditions of HT-N2O decomposition. Microporous and Mesoporous Materials, 281, 15-22).
[0007] The presence of cations (especially iron) promotes decomposition, but increasing the cation content to more than 1% does not seem to improve the activity of Fe-BEA zeolite (Chen, B., Liu, N., Liu, X., Zhang, R., Li, Y., Li, Y., & Sun, X. (2011), Study on the direct decomposition of nitrous oxide over Fe-beta zeolites: From experiment to theory, Catalysis today, 175(1), 245-255).
[0008] Sazama et al. (Sazama, P., Wichterlová, B., Tábor, E., P., Sathu, NK, Sobalík, Z., ... & Vondrová, A. (2014), Tailoring of the structure of Fe-cationic species in Fe-ZSM-5 by distribution of Al atoms in the framework for N2O decomposition and NH3-SCR-NOx, Journal of catalysis, 312, 123-138) The redox behavior of iron species in Fe-ZSM-5 catalysts in N2O decomposition and NH3-SCR-NOx was analyzed.
[0009] NOx and N2O can be reduced simultaneously in one reactor. Taking nitric acid plant as an example, Groves et al. (Michael C.E. Groves & Alexander Sasonow (2010) Uhde Technologies for the reduction of NOX and N2O emissions: Contribution to reducing emissions from nitric acid plants (Uhde technology for NOX and N2O abatement: a contribution to reducing emissions from nitric acid plants), Journal of Integrative Environmental Sciences, 7: S1, 211-222) tested different configurations: a N2O decomposition stage combined with an NH3-SCR stage; a deNOx stage followed by N2O reduction with ammonia or hydrocarbons (methane or propane).
[0010] It is known that Nu-86 type zeolites can be used for NH3-SCR applications (US6126912), but no studies have evaluated the efficiency of the catalysts in de-N2O or simultaneous de-NOx / de-N2O operations. Summary of the invention
[0011] The applicant has found that a catalyst based on / comprising a Nu-86 zeolite prepared according to a specific synthesis method and based on iron as a transition metal exhibits excellent performance qualities in the simultaneous conversion of NOx and N2O. Its performance qualities are particularly superior to those obtained using prior art catalysts (such as catalysts based on iron-exchanged zeolites of the FER structure type) when converting NOx and N2O using a reducing agent, especially in the temperature range of 300 to 500°C. The properties of the direct decomposition of N2O using this catalyst are also particularly superior from 450°C.
[0012] The present invention relates to a method for preparing a catalyst based on Nu-86 structural type zeolite and iron, comprising at least the following steps:
[0013] i) in an aqueous medium, the following substances are mixed: at least one silicon (Si) source in the form of SiO2 oxide; at least one aluminum (Al) source in the form of Al2O3 oxide; a nitrogen-containing organic compound R, R is octamethylammonium bromide (OctBr2); at least two sodium sources, one of which is sodium bromide (NaBr), and the molar composition of the reaction mixture is as follows:
[0014] SiO2 / Al2O3 is between 8 and 20,
[0015] H2O / SiO2 is between 15 and 60,
[0016] R / SiO2 is between 0.05 and 0.35,
[0017] Na2O / SiO2 is between 0.05 and 0.3,
[0018] NaBr / SiO2 is between 0.01 and 0.1, including the limit value,
[0019] Step i) is carried out for 5 to 15 minutes until a homogeneous mixture called precursor gel is obtained;
[0020] ii) ripening the precursor gel obtained in step i) at a temperature of 20 to 100° C., with or without stirring, for a period of 10 minutes to 48 hours, preferably 18 to 24 hours;
[0021] iii) subjecting the precursor gel obtained in step ii) to a hydrothermal treatment at a temperature of 120° C. to 220° C., preferably 140° C. to 195° C., for a duration of 12 hours to 35 days, preferably 12 hours to 33 days, until the Nu-86 zeolite is formed;
[0022] iv) at least one ion exchange consisting of contacting said dried zeolite obtained at the end of the previous step with a solution containing at least one substance capable of releasing iron in a reactive form in solution, at a temperature ranging from 20 to 95° C., preferably from 40 to 90° C., with stirring for a period ranging from 1 hour to 2 days;
[0023] v) thermal treatment by drying the Nu-86 zeolite obtained in the previous step at a temperature ranging from 20 to 150° C. for a period ranging from 2 to 24 hours, followed by at least one calcination at a temperature ranging from 400 to 700° C. in a stream of air for a period ranging from 2 to 20 hours.
[0024] Steps iv) and v) may be interchanged in order and optionally repeated.
[0025] In this case, the Nu-86 zeolite obtained in step iii) can be directly subjected to the heat treatment of step v), and then subjected to at least one ion exchange with an acid or compound (such as ammonium chloride, ammonium sulfate or ammonium nitrate) to obtain a protonated form of calcined Nu-86 zeolite, and then subjected to ion exchange with iron in step iv).
[0026] Seed crystals of Nu-86 structural type zeolite may be added to the reaction mixture of step i) in an amount ranging from 0.01% to 10% of the total mass of the sources of oxides of tetravalent (Si) and trivalent (Al) elements (SiO2 and Al2O3) in anhydrous form used in the reaction mixture, the seed crystals not being included in the total mass of the sources of tetravalent and trivalent elements.
[0027] The content of iron introduced by the ion exchange step iv) is from 0.5 to 6 mass %, preferably from 0.5 to 5 mass %, more preferably from 1 to 4 mass %, relative to the total mass of the anhydrous final catalyst.
[0028] The present invention also relates to a catalyst based on Nu-86 zeolite and iron for decomposing N2O or reducing N2O using a reducing agent such as NH3 or H2 or simultaneously reducing NOx and N2O, said catalyst being obtainable or directly obtainable by a preparation method according to any variant thereof.
[0029] The content of iron in the catalyst may be 0.5 to 6 mass %, preferably 0.5 to 5 mass %, more preferably 1 to 4 mass %, relative to the total mass of the anhydrous final catalyst.
[0030] The invention also relates to a method for decomposing N2O or reducing N2O using a reducing agent such as NH3 or H2 or for the simultaneous reduction of NOx and N2O, wherein the gas to be treated is brought into contact with a catalyst according to any of the variants described.
[0031] The catalyst may be formed by deposition in the form of a coating on a honeycomb or plate structure, or the catalyst may be in the form of extrudates or beads, wherein the catalyst content is up to 100%.
[0032] The honeycomb structure may be formed of parallel channels open at both ends or may include porous filter walls, in which case adjacent parallel channels are alternately blocked at either end of the channels.
[0033] For a filtering structure, the amount of catalyst deposited on the structure may be 50 to 250 g / L, and for a structure with open channels, the amount of catalyst deposited on the structure may be 80 to 300 g / L.
[0034] The catalyst can be combined with a binder (e.g. cerium oxide, zirconium oxide, aluminum oxide, non-zeolitic silicon-aluminum oxide, titanium oxide, cerium-zirconium type mixed oxide, tungsten oxide and / or spinel) so as to be formed by deposition in the form of a coating, and it is possible that the coating is preferably combined with other coatings having the ability to adsorb pollutants (especially NOx), reduce pollutants (especially NOx) or promote the oxidation of pollutants.
[0035] The catalyst can be integrated into the following devices:
[0036] - the exhaust pipe of an internal combustion engine powered by carbon-based or non-carbon-based fuels, or
[0037] - Reactors for treating industrial flue gases.
[0038] List of Figures
[0039] Other features and advantages of the method for preparing a catalyst according to the present invention will become apparent after reading the following non-limiting exemplary embodiments described with reference to the accompanying drawings.
[0040] Figure 1 The X-ray diffraction (XRD) pattern of the Nu-86 zeolite-based and iron-containing catalyst Fe—Nu-86 obtained according to Example 1 is shown. DETAILED DESCRIPTION
[0041] The present invention relates to a method for preparing a catalyst based on Nu-86 zeolite and iron, comprising at least the following steps:
[0042] i) in an aqueous medium, at least one silicon (Si) source in the form of SiO2 oxide, at least one aluminum (Al) source in the form of Al2O3 oxide, a nitrogen-containing organic compound R, R is octamethylammonium bromide (OctBr2), and at least two sodium sources, one of which is sodium bromide (NaBr), are mixed, and the molar composition of the reaction mixture is as follows:
[0043] SiO2 / Al2O3 is between 8 and 20,
[0044] H2O / SiO2 is between 15 and 60,
[0045] R / SiO2 is between 0.05 and 0.35,
[0046] Na2O / SiO2 is between 0.05 and 0.3,
[0047] NaBr / SiO2 is between 0.01 and 0.1, including the limit value,
[0048] Step i) is carried out for 5 to 15 minutes until a homogeneous mixture called precursor gel is obtained;
[0049] ii) ripening the precursor gel of step i) at a temperature of 20 to 100° C., with or without stirring, for a period of 10 minutes to 48 hours, preferably 18 to 24 hours;
[0050] iii) hydrothermally treating the precursor gel obtained in step ii) at a temperature of 120° C. to 220° C. for a period of 12 hours to 35 days until the Nu-86 zeolite is formed;
[0051] iv) at least one ion exchange, comprising contacting the Nu-86 zeolite obtained in the previous step with a solution containing at least one substance capable of releasing a transition metal (especially iron) in a reactive form in solution and stirring at a temperature of 20 to 95° C., preferably 40 to 90° C., for a period of 1 hour to 2 days;
[0052] v) thermal treatment by drying the Nu-86 zeolite obtained in the previous step at a temperature ranging from 20 to 150°C and subsequently calcining at least once at a temperature ranging from 400 to 700°C in an air stream.
[0053] Steps iv) and v) may be interchanged in order and optionally repeated.
[0054] In this case, the Nu-86 zeolite obtained in step iii) can be directly subjected to the heat treatment of step v), and then ion exchanged with an acid or compound (such as ammonium chloride, ammonium sulfate or ammonium nitrate) to obtain a protonated form of calcined Nu-86 zeolite, and then subjected to ion exchange with iron in step iv).
[0055] Seed crystals of Nu-86 zeolite are then added to the reaction mixture of step i), preferably in an amount of 0.01% to 10% by weight of the total mass of the tetravalent and trivalent element sources present in anhydrous form in the mixture, the seed crystals not being included in the total mass of the SiO2 and Al2O3 sources.
[0056] Step i) may include the step of ripening the reaction mixture at a temperature of 20 to 100° C., with or without stirring, for 30 minutes to 48 hours.
[0057] The hydrothermal treatment of step iii) may be carried out under autogenous pressure at a temperature of 120 to 220° C., preferably 140 to 195° C., for a duration of 12 hours to 35 days, preferably 12 hours to 33 days.
[0058] Advantageously, the Nu-86 zeolite obtained after step iii) is filtered, washed and dried at a temperature of 60 to 120° C. for 5 to 24 hours to obtain dried Nu-86 zeolite.
[0059] The ion exchange step iv) can be carried out by contacting the solid with a solution containing a single substance capable of releasing a transition metal, or by contacting the solid successively with different solutions, each solution containing at least one (preferably a single) substance capable of releasing a transition metal, the transition metal being iron.
[0060] Advantageously, the iron content introduced by ion exchange step iv) is between 0.5% and 6% by mass, preferably between 0.5% and 5% by mass, more preferably between 1% and 4% by mass, relative to the total mass of the anhydrous final catalyst.
[0061] Advantageously, the thermal treatment step v) comprises drying the solid at a temperature ranging from 20 to 150° C., preferably from 60 to 100° C., for a period of 2 to 24 hours, followed by at least one calcination in optionally dried air at a temperature ranging from 400 to 700° C., preferably from 500 to 600° C., for a period of 2 to 20 hours, preferably from 5 to 10 hours, more preferably from 6 to 9 hours, the flow rate of the optionally dried air preferably being from 0.5 to 1.5 L / h / g of solid to be treated, more preferably from 0.7 to 1.2 L / h / g of solid to be treated.
[0062] The invention also relates to a catalyst based on Nu-86 zeolite and iron capable of being or directly obtainable by said preparation method.
[0063] Advantageously, the content of iron in the catalyst obtained is between 0.5% and 6% by mass, preferably between 0.5% and 5% by mass, relative to the total mass of the anhydrous final catalyst.
[0064] The invention also relates to the use of a catalyst according to any of its variants or a catalyst obtainable or directly obtainable by the preparation process in the selective reduction of NOx using a reducing agent such as NH3 or H2.
[0065] The invention also relates to the use of the above catalyst or the catalyst which can be obtained or directly obtained by the preparation method for directly decomposing N2O or for simultaneously reducing NOx and N2O using a reducing agent (such as NH3 or H2).
[0066] The catalyst can be formed directly by extrusion into pellet form, or deposited in the form of a coating on a honeycomb structure or a plate structure.
[0067] The honeycomb structure may be formed of parallel channels open at both ends or may include porous filter walls, in which case adjacent parallel channels are alternately blocked at either end of the channels.
[0068] Advantageously, the amount of catalyst deposited on the structure may be between 50 and 200 g / L for a filtering structure and between 80 and 300 g / L for a structure with open channels.
[0069] The catalyst may be combined with a binder such as cerium oxide, zirconium oxide, aluminum oxide, non-zeolitic silicon-aluminum oxide, titanium oxide, cerium-zirconium type mixed oxide, tungsten oxide and / or spinel to facilitate formation in the form of a coating by deposition.
[0070] The coating may be combined with other coatings having the ability to adsorb pollutants (especially nitrogen oxides), reduce pollutants (especially NOx) or promote the oxidation of pollutants (such as CO or hydrocarbons).
[0071] The catalyst may be in the form of extrudates or beads, or any other form known to the person skilled in the art, wherein the catalyst content is up to 100%.
[0072] The support of the catalyst used in the process of the present invention can advantageously be formed by any technique well known to those skilled in the art. Advantageously, for example, it can be formed by extrusion, granulation, oil drop coagulation, rotating plate granulation or any other method well known to those skilled in the art. The support thus obtained can be of various shapes and sizes. Advantageously, the various components of the support or catalyst can be formed into a paste by a kneading step, and the resulting paste is then extruded, or by mixing powders and then granulating, or by any other known alumina-containing powder agglomeration method. The support thus obtained can be of various shapes and sizes. Preferably, the forming is carried out by kneading and extrusion.
[0073] In addition, as is well known to those skilled in the art, the use of additives is beneficial to facilitate shaping and / or improve the final mechanical properties of the carrier. Examples of additives that may be mentioned in particular include cellulose, carboxymethyl cellulose, carboxyethyl cellulose, tall oil, xanthan gum, surfactants, flocculants (such as polyacrylamide), carbon black, starch, stearic acid, polypropylene alcohol, polyvinyl alcohol, biopolymers, glucose, polyethylene glycol, etc.
[0074] Advantageously, water may be added or removed in order to adjust the viscosity of the paste to be extruded.This step may advantageously be carried out at any stage of the kneading step.
[0075] In order to adjust the solid content of the paste to be extruded so that it can be extruded, a predominantly solid compound can also be added, preferably an oxide or a hydrate. Preferably a hydrate is used, more preferably an aluminum hydrate. Advantageously, the hydrate has a loss on ignition greater than 15%.
[0076] The extrusion of the paste produced by the kneading step can be carried out using any conventional commercially available tool. The paste produced by the kneading is preferably extruded through a die, for example using a piston or a single-screw or twin-screw extruder. Any method known to those skilled in the art can be advantageously used for extrusion.
[0077] The carrier of the catalyst according to the present invention is generally in the form of a cylindrical extrudate or a polylobal extrudate, such as a straight or twisted bilobal, trilobal or polylobal extrudate, but may also be optionally manufactured and used in the form of crushed powder, sheets, rings, beads and / or wheels. Preferably, the carrier of the catalyst according to the present invention may be in the form of a sphere or an extrudate. Advantageously, the carrier may be in the form of an extrudate having a diameter of 0.5 to 5 mm, more particularly 0.7 to 2.5 mm. The molded body may be cylindrical (may be hollow or not hollow) and / or twisted and / or polylobal (e.g. 2, 3, 4 or 5 leaves) cylindrical and / or annular. Advantageously, polylobal form is preferably used.
[0078] The structure coated with the catalyst or obtained by extruding the catalyst can be integrated into the following devices:
[0079] - Exhaust pipes of internal combustion engines powered by carbon-based or non-carbon-based fuels (such as NH3, H2, etc., but not limited thereto);
[0080] - Reactors for the treatment of industrial flue gases. In nitric acid plants, it can be integrated into a tertiary stage, removing N2O by decomposition and NOx by adding a reducing agent such as NH3, or removing NOx and N2O simultaneously by adding a reducing agent.
[0081] catalyst
[0082] The catalyst according to the invention comprises at least one Nu-86 zeolite and iron.
[0083] The total content of iron is between 0.5% and 6% by mass, preferably between 0.5% and 5% by mass, relative to the total mass of the finished catalyst in anhydrous form.
[0084] The catalyst according to the invention may also contain further elements, such as alkali metals and / or alkaline earth metals, for example sodium, which originate in particular from compounds of the reaction medium of step i) of the process for the synthesis, in particular the preparation of the catalyst.
[0085] Method for preparing catalyst
[0086] Mixing step i)
[0087] Step i) Implementation:
[0088] i) in an aqueous medium, at least one silicon (Si) source in the form of SiO2 oxide, at least one aluminum (Al) source in the form of Al2O3 oxide, a nitrogen-containing organic compound R, R is octamethylammonium bromide (OctBr2), and at least two sodium sources, at least one of which is sodium bromide (NaBr), are mixed, and the molar composition of the reaction mixture is as follows:
[0089] SiO2 / Al2O3 is between 8 and 20,
[0090] H2O / SiO2 is between 15 and 60,
[0091] R / SiO2 is between 0.05 and 0.35,
[0092] Na2O / SiO2 is between 0.05 and 0.3,
[0093] NaBr / SiO2 is between 0.01 and 0.1, including the limit value,
[0094] wherein H2O corresponds to the molar amount of water in the reaction mixture, R corresponds to the molar amount of the nitrogen-containing organic compound, and Na2O corresponds to the molar amount expressed in the form of sodium oxide. After all components have entered the reaction mixture, step i) is carried out for a period of time so that a homogeneous mixture called precursor gel can be obtained, generally for 5 to 15 minutes.
[0095] The silicon source may be any of those commonly used in zeolite synthesis, such as powdered silica, silicic acid, colloidal silica, dissolved silica or tetraethoxysilane (TEOS). Among the powdered silicas, precipitated silicas, in particular those precipitated from alkali metal silicate solutions, fumed silica (e.g. Cab-O-Sil) and silica gel may be used.
[0096] Colloidal silica having various particle sizes (eg, average equivalent diameter of 10 nm to 15 nm or 40 nm to 50 nm), for example, those sold under registered trade names such as Ludox, may be used. Preferably, the silicon source is Aerosil 200.
[0097] According to the present invention, the aluminum source is preferably aluminum hydroxide or an aluminum salt (e.g., aluminum chloride, nitrate or sulfate), sodium aluminate, an aluminum alkoxide or aluminum oxide itself (preferably in hydrated or hydratable form, such as colloidal alumina, pseudoboehmite, gamma-alumina or alpha or beta alumina trihydrate). Mixtures of the above sources can also be used.
[0098] Step (i) of the process of the present invention comprises preparing an aqueous reaction mixture containing at least one silicon source, at least one aluminum source, at least one nitrogen-containing organic compound R, R being octamethylammonium bromide (OctBr2), and at least two sodium sources, one of which being sodium bromide (NaBr), to obtain a precursor gel of Nu-86 zeolite. The amounts of the reactants are adjusted as described above to produce a gel composition capable of crystallizing Nu-86 zeolite.
[0099] In step i) of the method of the present invention, it may be advantageous to add Nu-86 zeolite seeds to the reaction mixture, which can reduce the time required to form Nu-86 zeolite crystals and / or the total crystallization time. The seeds can also promote the formation of Nu-86 zeolite and reduce impurities. Such seeds include crystalline solids, especially crystals of Nu-86 zeolite. The seeds are usually added in a proportion of 0.01% to 10% of the total anhydrous mass of the tetravalent (Si) and trivalent (Al) element sources used in the reaction mixture, and the seeds are not included in the total mass of the tetravalent and trivalent element sources. When determining the composition of the above-mentioned reaction mixture and / or gel, that is, when determining the various molar ratios of the reaction mixture composition, the seeds are also not taken into account.
[0100] The mixing step i) is carried out until a homogeneous mixture is obtained, preferably for 5 to 15 minutes, preferably with stirring at low or high shear rate by any system known to those skilled in the art.
[0101] After step i), a uniform precursor gel can be obtained.
[0102] Step ii) Ripening of the Precursor Gel
[0103] Step ii) The reaction mixture is aged before hydrothermal crystallization to promote the formation of the Nu-86 zeolite and reduce impurities. In step ii) of the method of the present invention, the reaction mixture can be aged at ambient temperature or at a temperature of 20 to 100° C., with or without stirring, and advantageously lasts for 10 minutes to 48 hours, preferably 18 to 24 hours.
[0104] Hydrothermal treatment step iii)
[0105] According to step iii) of the method of the present invention, the precursor gel obtained after step ii) is subjected to a hydrothermal treatment, preferably at a temperature of 120° C. to 220° C. for a duration of 12 hours to 35 days, until the Nu-86 zeolite (or "crystalline solid") is formed.
[0106] Advantageously, the precursor gel is placed under hydrothermal conditions under autogenous reaction pressure, optionally with the addition of a gas such as nitrogen, at a temperature preferably between 120°C and 220°C, preferably between 140°C and 195°C, until the Nu-86 zeolite is completely crystallized.
[0107] The time required for crystallization is 12 hours to 35 days, preferably 12 days to 33 days.
[0108] The reaction is generally carried out with or without stirring, preferably with stirring. Any stirring system known to those skilled in the art may be used, such as pitched blades with counter-rotating blades, agitated turbine mixers or Archimedean screws.
[0109] Very advantageously, the process of the present invention forms a Nu-86 zeolite which is free of any other crystalline or amorphous phase.
[0110] After the hydrothermal treatment in step iii), the Nu-86 zeolite obtained may be filtered, washed and dried, preferably at a temperature of 60 to 120°C for a period of 5 to 24 hours, in order to obtain a dry Nu-86 zeolite prior to the ion exchange step iv).
[0111] It is also advantageous to obtain the protonated form of the Nu-86 zeolite after step iii). In this embodiment, the protonated form can be obtained by ion exchange with an acid (especially a strong mineral acid such as hydrochloric acid, sulfuric acid or nitric acid) or a compound (such as ammonium chloride, ammonium sulfate or ammonium nitrate) and then ion exchange with iron in step iv).
[0112] In this embodiment, the Nu-86 structure type zeolite obtained after step iii) is directly subjected to a heat treatment (step v), including drying at a temperature of 20 to 150° C., preferably 60 to 100° C., for a duration of 2 to 24 hours, and then calcining at least once in optionally dry air at a temperature of 400 to 700° C., preferably 500 to 600° C., for a duration of 2 to 20 hours, preferably 5 to 10 hours, more preferably 6 to 9 hours, and the flow rate of the optionally dry air is preferably 0.5 to 1.5 L / h / g of the solid to be treated, more preferably 0.7 to 1.2 L / h / g of the solid to be treated. Before calcination, the temperature can be gradually increased. Then, the dried and calcined Nu-86 zeolite is subjected to at least one ion exchange with an acid or compound (such as ammonium chloride, ammonium sulfate or ammonium nitrate) to obtain a protonated form of the calcined Nu-86 zeolite, and then subjected to step iv) of ion exchange with iron.
[0113] Ion exchange step iv)
[0114] The process for preparing the catalyst according to the invention comprises at least one ion exchange step, which consists in contacting the crystalline solid obtained at the end of the previous step, i.e. the Nu-86 zeolite obtained at the end of step iii), or the dried and calcined Nu-86 zeolite obtained at the end of step v) (in the preferred case where steps iv) and v) are reversed), or the dried, calcined and protonated Nu-86 zeolite, with at least one solution comprising at least one substance capable of releasing a transition metal in a reactive form in solution, in this case iron, with stirring at ambient temperature for a period ranging from 1 hour to 2 days, preferably from 0.5 days to 1.5 days, the concentration of the substance capable of releasing iron in the solution depending on the amount of iron to be incorporated into the crystalline solid.
[0115] The transition metal released in the exchange solution is iron.
[0116] According to the present invention, "a substance capable of releasing a transition metal" refers to a substance that can dissociate in an aqueous medium, such as a sulfate, nitrate, chloride, oxalate or an organic metal complex of a transition metal, or a mixture thereof. Preferably, the substance capable of releasing a transition metal is a sulfate or nitrate of the transition metal.
[0117] According to the invention, the solution contacted with the crystalline solid or the dried and calcined crystalline solid comprises at least one substance capable of releasing a transition metal, preferably a single substance capable of releasing a transition metal, in this case iron.
[0118] Advantageously, the process for preparing the catalyst according to the invention may comprise an ion exchange step iv), namely by contacting the crystalline solid with a solution containing a substance capable of releasing a transition metal, or by contacting the solid successively with a plurality of solutions, each containing a substance capable of releasing a transition metal, said metal being iron.
[0119] Advantageously, after the ion exchange is completed, the obtained solid is filtered, washed and then dried to obtain a powdered catalyst.
[0120] The total amount of iron contained in the final catalyst is between 0.5% and 6% by mass, relative to the total mass of the catalyst in anhydrous form.
[0121] According to one embodiment, the method for preparing the catalyst of the invention comprises an ion exchange step iv) of contacting the solid or the dried and calcined solid with a solution containing a substance capable of releasing iron in solution in a reactive form. Advantageously, in the final catalyst, i.e. at the end of the preparation method according to the invention, the total amount of iron present is between 0.5% and 6% by mass, preferably between 0.5% and 5% by mass, all percentages being by mass relative to the total mass of the final catalyst according to the invention in anhydrous form obtained at the end of the preparation method.
[0122] Heat treatment step v)
[0123] The preparation method according to the present invention comprises a heat treatment step v), which is carried out at the end of the previous step, i.e. at the end of the hydrothermal treatment step iii) or the ion exchange step iv), preferably at the end of the ion exchange step iv). The order of step iv) and step v) of the preparation process can be advantageously interchanged. It is also possible to optionally repeat the steps in step iv) and step v).
[0124] The heat treatment step v) comprises drying the solid at a temperature of 20 to 150° C., preferably 60 to 100° C., advantageously for a duration of 2 to 24 hours, and then calcining at least once in optionally dried air, advantageously at a temperature of 400 to 700° C., preferably 500 to 600° C., for a duration of 2 to 20 hours, preferably 5 to 10 hours, more preferably 6 to 9 hours, the flow rate of the optionally dried air being preferably 0.5 to 1.5 L / h / g of solid to be treated, more preferably 0.7 to 1.2 L / h / g of solid to be treated. Prior to calcination, the temperature may be gradually increased.
[0125] The catalyst obtained after the heat treatment step v) does not contain any organic matter, in particular, does not contain any organic structuring agent R.
[0126] In particular, the catalyst obtained by the above method comprising at least steps i), ii), iii), iv) and v) has improved N2O conversion performance.
[0127] Characterization of the catalyst prepared according to the invention
[0128] The catalyst comprises a zeolite of Nu-86 structure. This structure is characterized by X-ray diffraction (XRD).
[0129] X-ray diffraction (XRD) patterns were obtained by irradiating copper Kα1 The lattice spacing d of the sample was calculated using Bragg's law based on the position of the diffraction peak represented by the angle 2θ. hkl Features.d hkl The measurement error Δ(d hkl ) is calculated by Bragg's law and is a function of the absolute error Δ(2θ) of the measured value belonging to 2θ. An absolute error Δ(2θ) equal to ±0.02° is usually acceptable. The absolute error belonging to each d is measured by the height of the corresponding diffraction peak. hkl The relative intensity of the value I rel The X-ray diffraction pattern of the crystalline solid obtained at the end of step iii) of the process according to the invention comprises at least the d hkl and the average of the relative intensities) given in d hkl The value line. hkl In the Value column, the average value of the lattice spacing is in angstroms. Each of these values must be in to The measurement error Δ(d hkl )Inside.
[0130] Table 1
[0131]
[0132] VS = very strong; S = strong; m = medium; mw = slightly weak; w = weak; vw = very weak. Relative strength I rel It is given relative to a relative intensity scale, where the value of the most intense line of the X-ray diffraction pattern is 100: vw<15; 15≤w<30; 30≤mw<50; 50≤m<65; 65≤S<85; VS≥85.
[0133] The qualitative and quantitative analysis of the chemical substances present in the obtained material is carried out by X-ray fluorescence (XRF) spectroscopy. This is a chemical analysis technique that exploits the physical properties of matter (X-ray fluorescence). It enables the analysis of most chemical elements starting from Beryllium (Be) in concentrations ranging from the ppm level to 100%, with precise and reproducible results. The atoms in the sample are excited using X-rays, causing them to emit X-rays with energy characteristic of each element present. The intensity and energy of these X-rays are then measured to determine the concentration of the element in the material.
[0134] The loss on ignition (LOI) of the catalyst obtained after the drying step (and before calcination) of the process according to the invention or after the calcination step in step iv) is generally between 4% and 15% by weight. The loss on ignition of a sample, LOI for short, corresponds to the difference in mass of the sample before and after a thermal treatment at 1000° C. for 2 hours. It is expressed in %, corresponding to the percentage of mass loss. The loss on ignition generally corresponds to the loss of solvent contained in the solid, such as water, but also to the removal of organic compounds contained in the mineral solid fraction.
[0135] Use of the catalyst according to the invention
[0136] The invention also relates to the use of a catalyst according to the invention, directly or preparable by the above-described method, for the direct decomposition of N2O or the reduction of NOx and N2O by a reducing agent (such as NH3 or hydrocarbons), which catalyst can be formed by deposition in the form of a coating (or "washcoat") on a honeycomb structure (mainly for mobile applications) or a plate-like structure (especially for stationary applications). The invention can also be formed in the form of extrudates or beads. Preferably, the carrier of the catalyst according to the invention is in the form of a sphere or an extrudate. Advantageously, the carrier is in the form of an extrudate with a diameter of 0.5 to 5 mm, more particularly 0.7 to 2.5 mm. The molded body can be cylindrical (may be hollow or not hollow) and / or twisted and / or multi-lobed (for example 2, 3, 4 or 5 lobes) cylindrical and / or annular. Advantageously, multi-lobed forms are preferably used.
[0137] The honeycomb structure is formed by parallel channels that are open at both ends ("flow-through channels"), or includes porous filter walls, in which case adjacent parallel channels are alternately blocked at either end of the channel to force gas flow through the walls ("wall-flow monolith").
[0138] The honeycomb structure thus coated constitutes a catalytic block. The structure may comprise cordierite, silicon carbide (SiC), aluminum titanate (AlTi), alpha-aluminum oxide, mullite or any other material having a porosity of 30% to 70%. The structure may be formed in a metal sheet, in a stainless steel containing chromium and aluminum (FeCrAl steel).
[0139] The amount of catalyst according to the invention deposited on the structure is between 50 and 250 g / L for a filtering structure and between 80 and 300 g / L for a structure with open channels.
[0140] The actual coating ("carrier coating") comprises a catalyst according to the invention, advantageously a combination of a catalyst according to the invention and a binder (e.g. ceria, zirconia, alumina, non-zeolitic silica-alumina, titania, ceria-zirconia type mixed oxides, tungsten oxide, spinel). Advantageously, the coating is applied to the structure by a deposition method known as carrier coating, which consists in soaking the monolith in a suspension (or slurry) comprising a powdered catalyst according to the invention in a solvent (preferably water), and optionally a binder, a metal oxide, a stabilizer or other promoter. This soaking step can be repeated until the desired amount of coating is obtained. In some cases, the slurry can also be sprayed on the inside of the monolith. After deposition of the coating, the monolith is calcined at a temperature of 300 to 600°C for 1 to 10 hours.
[0141] The structure may be coated with one or more coatings. Advantageously, the coating comprising the catalyst according to the invention is combined with other coatings having the ability to adsorb pollutants (especially NOx), reduce pollutants (especially NOx) or promote the oxidation of pollutants (especially ammonia), i.e. covers other coatings or is covered by other coatings.
[0142] Another possibility is to prepare the catalyst as extrudates or beads or any other form known to the person skilled in the art. In this case, the structure formed may contain up to 100% of the catalyst according to the invention.
[0143] The support of the catalyst used in the process of the present invention can advantageously be formed by any technique well known to those skilled in the art. Advantageously, for example, it can be formed by extrusion, granulation, oil drop coagulation, rotating plate granulation or any other method well known to those skilled in the art. The support thus obtained can be of various shapes and sizes. Advantageously, the various components of the support or catalyst can be formed into a paste by a kneading step and then the resulting paste is extruded, or by mixing powders and then granulating, or by any other known alumina-containing powder agglomeration method. The support thus obtained can be of various shapes and sizes. Preferably, the forming is carried out by kneading and extrusion.
[0144] In addition, as is well known to those skilled in the art, the use of additives is beneficial to facilitate shaping and / or improve the final mechanical properties of the carrier. Examples of additives that may be mentioned in particular include cellulose, carboxymethyl cellulose, carboxyethyl cellulose, tall oil, xanthan gum, surfactants, flocculants (such as polyacrylamide), carbon black, starch, stearic acid, polypropylene alcohol, polyvinyl alcohol, biopolymers, glucose, polyethylene glycol, etc.
[0145] Advantageously, water may be added or removed in order to adjust the viscosity of the paste to be extruded.This step may be carried out at any stage of the kneading step.
[0146] In order to adjust the solid content of the paste to be extruded so that it can be extruded, a predominantly solid compound can also be added, preferably an oxide or a hydrate. Preferably a hydrate is used, more preferably an aluminum hydrate. Advantageously, the hydrate has a loss on ignition greater than 15%.
[0147] The extrusion of the paste produced by the kneading step can advantageously be carried out using any conventional commercially available tool. The paste produced by kneading is preferably extruded through a die, for example using a piston or a single-screw or twin-screw extruder. Any method known to those skilled in the art can advantageously be used for extrusion.
[0148] The carrier of the catalyst according to the present invention is generally in the form of cylindrical extrudates or polylobal extrudates, such as straight or twisted bilobes, trilobes or polylobal extrudates, but can also be optionally manufactured and used in the form of crushed powder, sheets, rings, beads and / or wheels. Preferably, the carrier of the catalyst according to the present invention is in the form of a sphere or an extrudate. Advantageously, the carrier is in the form of an extrudate with a diameter of 0.5 to 5 mm, more particularly 0.7 to 2.5 mm. The molded body can be cylindrical (can be hollow or not hollow) and / or twisted and / or polylobal (e.g. 2, 3, 4 or 5 leaves) cylindrical and / or annular. Advantageously, polylobal form is preferably used.
[0149] Advantages of the present invention
[0150] Compared with the catalysts of the prior art, the catalyst of the invention based on Nu-86 zeolite and iron has better performance in the removal of NOx and N2O. In gas streams containing high concentrations of N2O, the performance quality of the conversion of NOx and N2O using a reducing agent such as NH3 is particularly superior to that obtained using a catalyst based on a FER structural zeolite, especially in the temperature range of 300 to 500°C. The properties of the direct decomposition of N2O using the catalyst from 450°C are also particularly superior.
[0151] Example
[0152] Example 1: Preparation of a catalyst Fe-Nu-86 containing Nu-86 zeolite and iron according to the present invention
[0153] At ambient temperature, 271.72 g of an aqueous solution of octamethylammonium bromide (25 wt %, SACHEM) was mixed with 280.71 g of deionized water while stirring. At ambient temperature, 8.89 g of sodium hydroxide (98 wt %, Aldrich) was dissolved in the above mixture while stirring. Then, at room temperature, 2.39 g of sodium bromide (NaBr, Prolabo) was added while stirring. 4.13 g of sodium aluminate (NaAlO2, CARLO ERBA) and 140.4 g of deionized water were added to the synthetic mixture, and the synthetic mixture was stirred for half an hour at ambient temperature. When the obtained suspension was uniform, 41.8 g of fumed silica (Aerosil 200, Degussa) was immediately poured in, and the obtained suspension was vigorously stirred for 10 minutes at ambient temperature. The molar composition of the precursor gel is as follows: 1SiO2: 0.031Al2O3: 0.255OctaBr2: 0.2Na2O: 0.033NaBr: 50H2O, i.e., a SiO2 / Al2O3 ratio of 32.4. The homogenized precursor gel is then transferred to a 1000 mL stainless steel reactor equipped with a stirring system with four inclined blades, followed by a 24-hour aging step at ambient temperature while stirring at 180 rpm. After the aging step, the reactor is heated for 32 days, with the temperature increasing to 155°C at a rate of 0.4°C per minute while stirring at 300 rpm, thereby crystallizing the Nu-86 zeolite. The resulting crystalline product is filtered out, washed with deionized water, and then dried at 100°C for 12 hours. The solid was then introduced into a muffle furnace where a calcination step was carried out: the calcination cycle consisted of increasing the temperature at 1.5°C / min to 200°C, maintaining a stable temperature at 200°C for 2 hours, increasing the temperature at 1°C / min to 550°C, then maintaining a stable temperature at 550°C for 12 hours and then returning to ambient temperature.
[0154] After calcination, the zeolite was contacted with a 1M aqueous solution of NH4NO3 and stirred at 80°C for 1 hour. The ratio of solution volume to zeolite mass was 19 (V / W). The obtained solid was filtered and washed, and the exchange process was repeated again under the same conditions.
[0155] The obtained material was designated as NH4-Nu-86 and treated in a stream of dry air at 550°C for 4 hours with a temperature ramp of 1°C / min. The obtained material was the protonated form of Nu-86 zeolite (H-Nu-86).
[0156] The H-Nu-86 zeolite was then contacted with an aqueous solution of Fe(NO3)3·9H2O and stirred at 80°C for 17 hours, with a ratio of solution volume to zeolite mass equal to 200 (V / P). The solid was finally centrifuged and dried at 100°C overnight.
[0157] The solid obtained after contact with the Fe(NO3)3 solution was then calcined under a gas flow of 550°C for 8 hours with a temperature ramp of 1°C / min. The obtained material was named Fe-Nu-86.
[0158] The Fe-Nu-86 catalyst thus prepared contained 2.6 wt. % of iron relative to the total weight of the catalyst.
[0159] Through X-ray diffraction analysis, it was determined that the Fe-Nu-86 catalyst was mainly composed of Nu-86 zeolite with a purity of more than 99% by weight. The X-ray diffraction pattern of the catalyst Fe-Nu-86 is shown in Figure 1 The SiO2 / Al2O3 molar ratio of the product was 30 as determined by XRF.
[0160] Example 2: Commercial Fe-ferrierite (Fe-FER)
[0161] A commercial Fe-FER catalyst for removing NOx / N2O is provided. According to XRF measurement, the SiO2 / Al2O3 molar ratio of the product is 17.5, and the mass percentage of iron is 2%. The obtained catalyst is named Fe-FER.
[0162] Example 3: Conversion of NOx and N2O: Comparison of the catalyst of the present invention with the prior art
[0163] At different operating temperatures, catalytic tests were carried out on the catalyst synthesized according to Example 1 (Fe-Nu-86) and the catalyst synthesized according to Example 2 (Fe-FER) for the reduction of nitrogen oxides (NOx) and nitrous oxide (N2O) by ammonia (NH3) in the presence of oxygen (O2).
[0164] For each sample tested, 200 mg of the catalyst in powder form was placed in a quartz reactor into which 145 L / h of a gas mixture having the following molar composition was passed: 200 ppm NO, 200 ppm NO2, 200 ppm N2O, 800 ppm NH3, 8.5% O2, 9% CO2, 10% H2O, and the remainder N2.
[0165] An FTIR analyzer is used to measure the concentrations of NO, NO2, NH3, N2O, CO, CO2, H2O, and O2 at the reactor outlet. The calculation method for NOx conversion rate is as follows:
[0166] NOx conversion rate = (NOx inlet - NOx outlet) / NOx inlet
[0167] N2O conversion rate = (N2O inlet - N2O outlet) / N2O inlet
[0168] In these formulas, the import and export indices represent the contents before and after catalytic reduction, respectively.
[0169] The NOx conversion results are shown in Table 2 below:
[0170] Table 2
[0171] 300℃ 400℃ 450℃ 500℃ Fe-Nu-86 100% 100% 100% 100% Fe-FER 94% 100% 100% 100%
[0172] The N2O conversion results are shown in Table 3 below:
[0173] Table 3
[0174] 300℃ 400℃ 450℃ 500℃ Fe-Nu-86 0% 10% 31% 70% Fe-FER 0% 10% 31% 66%
[0175] The Fe-Nu-86 catalyst synthesized according to the present invention has better performance in NOx conversion than the Fe-FER catalyst, especially at low temperature (300°C). In terms of N2O conversion, the performance of the Fe-Nu-86 catalyst is similar to that of the Fe-FER catalyst, or even slightly better.
[0176] Example 4: Conversion of NOx and N2O: Comparison of the catalyst of the present invention with the prior art
[0177] At different operating temperatures, catalytic tests were carried out on the catalyst synthesized according to Example 1 (Fe-Nu-86) and the catalyst synthesized according to Example 2 (Fe-FER) for the reduction of nitrogen oxides (NOx) and nitrous oxide (N2O) by ammonia (NH3) in the presence of oxygen (O2).
[0178] For each sample tested, 200 mg of the catalyst in powder form was placed in a quartz reactor into which 145 L / h of a gas mixture having the following molar composition was passed: 200 ppm NO, 50 ppm NO2, 1000 ppm N2O, 1250 ppm NH3, 2.5% O2, 8% H2O, and the remainder N2.
[0179] An FTIR analyzer is used to measure the concentrations of NO, NO2, NH3, N2O, CO, CO2, H2O, and O2 at the reactor outlet. The calculation method for NOx conversion rate is as follows:
[0180] NOx conversion rate = (NOx inlet - NOx outlet) / NOx inlet
[0181] N2O conversion rate = (N2O inlet - N2O outlet) / N2O inlet
[0182] In these formulas, the import and export indices represent the contents before and after catalytic reduction, respectively.
[0183] The NOx conversion results are shown in Table 4 below:
[0184] Table 4
[0185] 300℃ 400℃ 450℃ 500℃ 600℃ Fe-Nu-86 54% 88% 100% 100% 100% Fe-FER 58% 92% 100% 100% 100%
[0186] The N2O conversion results are shown in the following table:
[0187] Table 5
[0188] 300℃ 400℃ 450℃ 500℃ 600℃ Fe-Nu-86 0% 15% 56% 86% 100% Fe-FER 0% 5% 35% 80% 97%
[0189] The Fe-Nu-86 catalyst synthesized according to the present invention provides better performance qualities for removing N2O than Fe-FER catalyst starting from lower temperature. It also provides very similar performance to Fe-FER catalyst in terms of NOx conversion.
Claims
1. A method for preparing a catalyst, wherein the catalyst comprises a Nu-86 structural type zeolite and iron, the method comprising at least the following steps: i) in an aqueous medium, the following substances are mixed: at least one silicon (Si) source in the form of SiO2 oxide, at least one aluminum (Al) source in the form of Al2O3 oxide, a nitrogen-containing organic compound R, R is octamethylammonium bromide (OctBr2), at least two sodium sources, one of which is sodium bromide (NaBr), the molar composition of the reaction mixture is as follows: SiO2 / Al2O3 is 8 to 20, H2O / SiO2 is 15 to 60, R / SiO2 is 0.05 to 0.35, Na2O / SiO2 is 0.05 to 0.3, NaBr / SiO2 is 0.01 to 0.1, both limits included, Step i) is carried out for 5 to 15 minutes until a homogeneous mixture called precursor gel is obtained; ii) ripening the precursor gel obtained in step i) at a temperature of 20 to 100° C., with or without stirring, for a period of 10 minutes to 48 hours, preferably 18 to 24 hours; iii) subjecting the precursor gel obtained in step ii) to a hydrothermal treatment at a temperature of 120° C. to 220° C., preferably 140° C. to 195° C., for a duration of 12 hours to 35 days, preferably 12 hours to 33 days, until the Nu-86 zeolite is formed; iv) at least one ion exchange, comprising contacting said zeolite obtained in the previous step with a solution containing at least one substance capable of releasing iron in a reactive form in solution at a temperature of 20 to 95° C., preferably 40 to 90° C., and stirring for a period of 1 hour to 2 days; v) thermal treatment, by drying the Nu-86 zeolite obtained at the end of the previous step at a temperature ranging from 20 to 150° C. for a period ranging from 2 to 24 hours, followed by at least one calcination at a temperature ranging from 400 to 700° C. in a stream of air for a period ranging from 2 to 20 hours.
2. The method of claim 1, wherein: Steps iv) and v) are interchanged in order and optionally repeated.
3. The preparation method according to claim 2, wherein The Nu-86 zeolite obtained in step iii) is directly subjected to the heat treatment of step v), and then subjected to at least one ion exchange with an acid or compound such as ammonium chloride, ammonium sulfate or ammonium nitrate to obtain a protonated form of calcined Nu-86 zeolite, which is then subjected to ion exchange with iron in step iv).
4. The preparation method according to any one of the preceding claims, wherein: Seed crystals of Nu-86 structural type zeolite are added to the reaction mixture of step i) in an amount ranging from 0.01% to 10% of the total mass of the sources of oxides of tetravalent (Si) and trivalent (Al) elements (SiO2 and Al2O3) in anhydrous form used in the reaction mixture, the seed crystals not being included in the total mass of the sources of tetravalent and trivalent elements.
5. The preparation method according to any one of the preceding claims, wherein: The content of iron introduced by the ion exchange step iv) is from 0.5 to 6 mass %, preferably from 0.5 to 5 mass %, more preferably from 1 to 4 mass %, relative to the total mass of the anhydrous final catalyst.
6. A catalyst based on Nu-86 zeolite and iron for decomposing N2O or reducing N2O using a reducing agent such as NH3 or H2 or simultaneously reducing NOx and N2O, the catalyst being capable of being or directly obtained by the preparation method according to any one of claims 1 to 5.
7. The catalyst according to claim 6, wherein The total content of iron is 0.5 to 6 mass %, preferably 0.5 to 5 mass %, more preferably 1 to 4 mass %, relative to the total mass of the anhydrous final catalyst.
8. A method for decomposing N2O or reducing N2O using a reducing agent such as NH3 or H2 or simultaneously reducing NOx and N2O, wherein the gas to be treated is brought into contact with a catalyst as claimed in any one of claims 6 and 7.
9. The method for decomposing N2O or reducing N2O or simultaneously reducing NOx and N2O as claimed in claim 8, wherein the catalyst is deposited in the form of a coating on a honeycomb structure or a plate structure, or the catalyst is in the form of extrudates or beads, wherein the content of the catalyst is up to 100%.
10. The method for decomposing N2O or reducing N2O or simultaneously reducing NOx and N2O according to claim 9, wherein: The honeycomb structure is formed by parallel channels open at both ends or includes porous filter walls. In the case of including porous filter walls, adjacent parallel channels are alternately blocked at either end of the channels.
11. The method for decomposing N2O or reducing N2O or simultaneously reducing NOx and N2O according to claim 10, wherein: The amount of catalyst deposited on the structure is 50 to 250 g / L for a filtering structure and 80 to 300 g / L for a structure with open channels.
12. A method for decomposing N2O or reducing N2O or simultaneously reducing NOx and N2O as claimed in any one of claims 9 to 11, wherein the catalyst is combined with a binder, such as cerium oxide, zirconium oxide, aluminum oxide, non-zeolitic silicon-aluminum oxide, titanium oxide, cerium-zirconium type mixed oxide, tungsten oxide and / or spinel, so as to be formed in the form of a coating by deposition, and it is possible that the coating is preferably combined with other coatings having the ability to adsorb pollutants, especially NOx, reduce pollutants, especially NOx or promote the oxidation of pollutants.
13. The method for decomposing N2O or reducing N2O or simultaneously reducing NOx and N2O according to any one of claims 8 to 12, wherein: The catalyst is integrated into the following device: - the exhaust pipe of an internal combustion engine powered by carbon-based or non-carbon-based fuels, or - Reactors for treating industrial flue gases.
Citation Information
Patent Citations
Process and catalyst comprising at least one EU-1 and / or NU-86 and / or NU-87 zeolite for reducing oxides of nitrogen in an oxidizing medium
US6126912A